2015
DOI: 10.17352/2455-5282.000019
|View full text |Cite
|
Sign up to set email alerts
|

Middle Aortic Syndrome: A Case Report and Review of the Literature

Abstract: Central aortic stiffness was evaluated by Sphygmocor device using intersecting tangent algorithm and substructed path length method. Both indices, carotid-femoral Pulse Wave Velocity and Augmentation Index were normal (6.5 m/sec and 36%, respectively). Carotid ultrasound, unexpectedly, revealed diffusely increased Intima Media Thickness of the carotid artery wall (bilaterally mean 1.1-1.2 mm) and presence of two discrete isoechogenic plaques

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…MAS, also known as aortic coarctation or aortic hypoplasia, may be classified into either suprarenal (70%), infrarenal (7%), or intrarenal (23%) manifestations. 3 Renal and visceral artery involvement is seen in 80% and 22%, respectively, 3 which was not observed in this patient. The average age of diagnosis is 7 years old.…”
Section: Discussionmentioning
confidence: 52%
“…MAS, also known as aortic coarctation or aortic hypoplasia, may be classified into either suprarenal (70%), infrarenal (7%), or intrarenal (23%) manifestations. 3 Renal and visceral artery involvement is seen in 80% and 22%, respectively, 3 which was not observed in this patient. The average age of diagnosis is 7 years old.…”
Section: Discussionmentioning
confidence: 52%
“…The coarctation may be several centimetres long or short and 'web-like'. 5 A systematic review of the middle aortic syndrome in children found 64% to be idiopathic, 15% to be genetic (including neurofibromatosis and William's syndrome), 17% to be inflammatory (such as Takayasu's disease) and 4% due to fibromuscular dysplasia. 6 The morphology was not reported in 62% of patients in this systematic review, but of those in whom the morphology was available, 60% had a discrete segmental narrowing (some of which may have resulted in a web-like appearance).…”
mentioning
confidence: 99%